Mediating each other's learning: The peer tutor learning model and student learning outcomes - Ramadanis, Resi; Montessori, Maria (Indonesian Research Journal in Education |IRJE|, 2025)
This research aims to determine whether learning with the peer tutor model effectively improves student learning outcomes in social studies at Adabiah Padang Junior High School. This research uses a quantitative design. The research subjects were grade VIII students at Adabiah Padang Junior High School, which had 80 students. Data were collected using direct observation methods, observation sheets, and in the form of test questions. The collected data was analyzed using descriptive analysis, and the average score and the percentage completeness of student learning outcomes were calculated. Based on the research results, the value of learning outcomes and student completeness has increased. The post-test results in the three classes show an increase in the average of the three classes and the number of students or the percentage of complete students. Only a few students did not reach the minimum completeness after implementing the peer tutor learning model. Peer tutoring on student learning outcomes is practical enough for social studies learning.